Awareness of Periodontal Medicine among Medical Students at a Tertiary Care Center - Rajkarnikar, Junima; Acharya, Jemish; Yadav, Karnika (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Introduction: Tissue destruction of supporting periodontal tissues is mediated by an overreactive immune inflammatory response to bacteria in the subgingival environment. Tissue destruction in periodontitis occurs by the stimulatory action of pro inflammatory cytokines and proteolytic enzymes released by neutrophils, macrophages, and the action of bone resorption mediators, all of which are being regulated by B and T cells. Periodontitis act as a focus of infection and bacteria metastases through blood stream to various vital organs like heart, lungs, joints and amniotic fluid. Objective: To assess the awareness of periodontal medicine among medical students at a tertiary care center in Kathmandu. Methods: A total of 115 subjects were taken for the present study. Data was collected using a questionnaire which included questions used to assess the knowledge about periodontal diseases and its possible effects on systemic conditions. Results: Out of the total participants, 58 (50.4%) said that periodontal disease was not related to coronary heart diseases. Only 14 (12.2%) had an idea about the association of pre-term birth and periodontitis. While 86 (74.8%) knew the impact of diabetes on periodontium, only 34 (29.6%) said that there was an association between periodontitis and hospital acquired pneumonia. Conclusion: Knowledge about the association of periodontal disease with various systemic conditions is not satisfactory among the various medical students of this hospital.